Proteinuria and sirolimus after renal transplantation: a retrospective analysis from a large German multicenter database. (26th December 2013) - Naik, Marcel G.; Heller, Katharina M.; Arns, Wolfgang; Budde, Klemens; Diekmann, Fritz; Eitner, Frank; Fischereder, Michael; Goßmann, Jan; Heyne, Nils; Morath, Christian; Riester, Udo; Gwinner, Wilfried; et al.
Abstract The German Sirolimus Study Group has established a database among 10 transplant centers throughout Germany to study the outcomes in 726 renal transplant patients being converted to a sirolimus‐containing therapy between 2000 and 2008 with a total of more than 1500 recorded patient years on therapy. In this study, we present a detailed description of the cohort, of characteristic changes over the observation period, proteinuria and graft survival, and new‐onset proteinuria after conversion. Over the study period, age, graft function at the time of conversion, and the proportion of patients switched to sirolimus because of malignancy increased, whereas the proportion of patients with significant proteinuria at conversion decreased. Already modest proteinuria (151–268 mg/L) at conversion and new‐onset proteinuria (>500 mg/L) after conversion were associated with inferior graft survival. Even mild proteinuria (>71 mg/L) at conversion was associated with new‐onset proteinuria (>500 mg/L) post‐conversion. Serum creatinine and urinary protein excretion at conversion together with age at transplantation had a significant impact on patient and graft survival. This large data set confirms and extends previous observations that proteinuria is an important indicator for graft outcome after conversion to sirolimus. We conclude that patients without any proteinuria have the greatest benefit from conversion to sirolimus.